Enhanced In Vitro Antitumor Activity of GnRH-III-Daunorubicin Bioconjugates Influenced by Sequence Modification - Sabine Schuster; Beáta Biri-Kovács; Bálint Szeder; László Buday; János Gardi; Zsuzsanna Szabó; Gábor Halmos; Gábor Mező (MDPI AG, 2018)
Receptors for gonadotropin releasing hormone (GnRH) are highly expressed in various human cancers including breast, ovarian, endometrial, prostate and colorectal cancer. Ligands like human GnRH-I or the sea lamprey analogue GnRH-III represent a promising approach for the development of efficient drug delivery systems for targeted tumor therapy. Here, we report on the synthesis and cytostatic effect of 14 oxime bond-linked daunorubicin GnRH-III conjugates containing a variety of unnatural amino acids within the peptide sequence. All compounds demonstrated a reduced cell viability in vitro on estrogen receptor α (ERα) positive and ERα negative cancer cells. The best candidate revealed an increased cancer cell growth inhibitory effect compared to our lead-compound GnRH-III-[4Lys(Bu),8Lys(Dau=Aoa)]. Flow cytometry and fluorescence microscopy studies showed that the cellular uptake of the novel conjugate is substantially improved leading to an accelerated delivery of the drug to its site of action. However, the release of the active drug-metabolite by lysosomal enzymes was not negatively affected by amino acid substitution, while the compound provided a high stability in human blood plasma. Receptor binding studies were carried out to ensure a high binding affinity of the new compound for the GnRH-receptor. It was demonstrated that GnRH-III-[2ΔHis,3d-Tic,4Lys(Bu),8Lys(Dau=Aoa)] is a highly potent and promising anticancer drug delivery system for targeted tumor therapy.